2016
DOI: 10.3109/09273948.2016.1158283
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 Anterior Uveitis: Immunology and Immunopathology

Abstract: Acute anterior uveitis (AAU) is the commonest type of uveitis and HLA-B27 AAU is the most frequently recognized type of acute anterior uveitis and anterior uveitis overall. Recent evidence indicates that acute anterior uveitis is a heterogenous disease, is polygenic and is frequently associated with the spondyloarthropathies (SpA). Studies of patients with AAU and animal models of disease indicate a role for innate immunity, the IL-23 cytokine pathway and exogenous factors, in the pathogenesis of both SpA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 95 publications
0
42
1
3
Order By: Relevance
“…In terms of anatomy, anterior uveitis is the most common, accounting for 50–65% of cases seen in Australian tertiary referral centres, with HLA‐B27 associated uveitis comprising 18–32% of these cases …”
Section: Classification and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of anatomy, anterior uveitis is the most common, accounting for 50–65% of cases seen in Australian tertiary referral centres, with HLA‐B27 associated uveitis comprising 18–32% of these cases …”
Section: Classification and Epidemiologymentioning
confidence: 99%
“…7 In terms of anatomy, anterior uveitis is the most common, accounting for 50-65% of cases seen in Australian tertiary referral centres, 8 with HLA-B27 associated uveitis comprising 18-32% of these cases. 9 Uveitis is the most frequent ocular manifestation of sarcoidosis, occurring in 30-60% of sarcoidosis patients and representing 2-15% of all uveitis patients referred to tertiary centres. 10 Relapsing-remitting panuveitis or posterior uveitis is the primary ocular involvement in Behcet disease (BD), occurring in 50-70% of patients.…”
Section: Classification and Epidemiologymentioning
confidence: 99%
“…Additionally vascular abnormalities and endothelial dysfunction are considered to play a role in the pathogenesis of AAU, IBD, and psoriasis [1820]. …”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies furthermore showed that gut bacteria, such as Yersinia Enterocolitica and Salmonella typhimurium, are involved in the pathogenesis of SpA. 5,16 Significantly decreased genera such as Roseburia and butyrate production have been observed in Behçet patients as compared with healthy controls. 17 Commensal bacteria are thought to be a potential trigger and a factor which can influence the development of disease in experimental autoimmune uveitis (EAU).…”
mentioning
confidence: 99%
“…1,2 Acute anterior uveitis is the most common uveitis entity, 3 which is often accompanied with other systemic diseases such as ankylosing spondylitis (AS) and spondyloarthropathies (SpA). 4,5 Previous studies have shown that undiagnosed SpA occurs in about 40% of patients with idiopathic AAU. 6 The human leucocyte antigen B27 (HLA-B27) has been shown to have a strong association with AAU.…”
mentioning
confidence: 99%